2020
DOI: 10.3389/fimmu.2020.565275
|View full text |Cite
|
Sign up to set email alerts
|

Innate Lymphocytes in Inflammatory Arthritis

Abstract: Inflammatory arthritis (IA) refers to a group of chronic diseases, including rheumatoid arthritis (RA), psoriatic arthritis (PsA), ankylosing spondylitis (AS), and other spondyloarthritis (SpA). IA is characterized by autoimmune-mediated joint inflammation and is associated with inflammatory cytokine networks. Innate lymphocytes, including innate-like lymphocytes (ILLs) expressing T or B cell receptors and innate lymphoid cells (ILCs), play important roles in the initiation of host immune responses against sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 147 publications
(170 reference statements)
0
15
0
1
Order By: Relevance
“…RA results from the loss of immune self-tolerance, autoantigen presentation, and aberrant inflammatory cytokine production caused by abnormal activation of innate and adaptive immune systems (101). Although adaptive immunity (e.g., autoantibody production mediated by CD4 + T cells and B cells) predominates, innate immune cells (e.g., DCs, macrophages, mast cells, and NK cells) have also been implicated in RA pathogenesis (98,102,103).…”
Section: Nk Cells and Rheumatoid Arthritis (Ra)mentioning
confidence: 99%
“…RA results from the loss of immune self-tolerance, autoantigen presentation, and aberrant inflammatory cytokine production caused by abnormal activation of innate and adaptive immune systems (101). Although adaptive immunity (e.g., autoantibody production mediated by CD4 + T cells and B cells) predominates, innate immune cells (e.g., DCs, macrophages, mast cells, and NK cells) have also been implicated in RA pathogenesis (98,102,103).…”
Section: Nk Cells and Rheumatoid Arthritis (Ra)mentioning
confidence: 99%
“…These studies highlight the role of IL-9 in the resolution of inflammation in arthritis [130]. In human studies, IL-9-producing IL-C2 cells were also identified in the PBMCs of RA patients [130,131]. In a study of treatment-induced remission of RA, synovial fluid of patients showed high levels of IL-9 [128].…”
Section: Rheumatoid Arthritis (Ra)mentioning
confidence: 83%
“…Type 2 innate lymphoid cells (IL-C2) are documented to express IL-9 and have an anti-inflammatory function [128,129]. These studies highlight the role of IL-9 in the resolution of inflammation in arthritis [130]. In human studies, IL-9-producing IL-C2 cells were also identified in the PBMCs of RA patients [130,131].…”
Section: Rheumatoid Arthritis (Ra)mentioning
confidence: 93%
“…As a messenger between the innate and adaptive immune systems, innate lymphoid cells (ILCs) have been realized to be intensely involved in the pathogenesis of inflammatory arthritis ( 52 , 53 ). In particular, ILC2 acts as a crucial regulator in damping joint inflammation in contrast to proinflammatory ILC1/ILC3.…”
Section: Ilc2–eosinophil–m2 Macrophage Axis Counteracts Joint Inflammationmentioning
confidence: 99%